KONSUMSI KAFEIN BERPENGARUH TERHADAP KEJADIAN PREMENSTRUAL SYNDROME: Caffeine Consumption Affecting The Incident of Premenstrual Syndrome - Woro Tri Utami; Wiqodatul Ummah (ASSYIFA : Jurnal Ilmu Kesehatan, 2023)
Premenstrual syndrome (PMS) is a group of symptoms in the form of physical and psychological changes experienced by women 7-10 days before menstruation and disappear a few days after menstruation. Complaints can vary, they can be milder or more severe, resulting in mental disorders (irritability, sensitivity) or physical disorders. One of the factors that influence the occurrence of premenstrual syndrome (PMS) is the habitual factor, namely caffeine consumption. Consuming excessive amounts of caffeine can cause effects, one of which is premenstrual syndrome (PMS). Symptoms of premenstrual syndrome are experienced by around 65.7% of adolescent girls. The aim of this research is to determine the influence of caffeine consumption factors on the incidence of premenstrual syndrome in young women in Tlogomas Village, Malang City. This research is a descriptive-analytic study with a cross-sectional approach. The population in this study was 657 young women in Tlogomas Village, Malang City. The sample in this study was 87 young women in Tlogomas Village, Malang City. The sampling technique used is simple random sampling. Determination of sample size using the Slovin formula. Data were analyzed using the chi-square test. This research shows that there is a significant influence between caffeine consumption and the incidence of premenstrual syndrome as evidenced by a p value of <0.001 (p<0.05).